IMPLEMENTATION OF RME MODEL ASSISTANCE E-LEARNING TO IMPROVE SKILLS OF STUDENT PROCESS IN COURSE INTRODUCTION PROBABILITY - Iswahyudi Joko S; Abdul Rohman (Universitas Muhammadiyah Semarang, 2018)
In the teaching and learning process the lecturer occupies a very central position, because its role is very decisive. Lecturers must be able to translate and describe the content contained inthe curriculum, then transform the contents to the students through the process of teaching andlearning. Apart from that, improving and developing the quality of education is alwaysexpected. Therefore, the way of improvement and development is also a problem for us all.Neither government, society, nor individual should feel obliged to endure it. In learning,science and technology great role to promote a country. To be an advanced country, the nationmust be ingenious, clever and a lot of knowledge, both social science, natural science,introduction of probability and other sciences that are skilled. Without prejudice to any otherknowledge, the role of introductory probability is likely to be very important and needsserious handling. Introduction probability is a discipline that has a characteristic comparedwith the discipline of science. Therefore, learning and teaching activities required a method,given the different students of different levels of ability. Introduction probability arisesbecause of human thoughts associated with ideas, processes and reasoning. Learning on thematerial still uses expository methods. In this research, Realistic Matematics Education(RME) model with E-learning will be used.